Pendidikan Islam dalam Memperkukuh Etika dan Moral - Sukatin; Marzani; Fina Nabila; Eni Mardila; M. Khoitil Abyad (Medan Resource Center, 2022)
The problems faced by educational institutions are more complicated. One of them is the quality of all the level education have not increased. The increasing quality of Islamic educational institutions is something absolut because it is a part pf educational nitional system. The increasing quality of the institutions have a purpose to give a guarantee to the people, a guarantee that the implementation of the education appropriates with what must be happen and wished by the people. Based on its characteristic, Islamic educational institutions not only create the potential intellectually figure (intellectual oriented), but also create the character and ethical figure. The main concern of the Islamic educational institution is the improvenment of both body and spirit.